Expressionist Narrative of War (Vasyl Stefanyk’s Novellas in the Western European Context) - Shvets, Alla (Verbum, 2021)
This article shows how the influence of Western European expressionism on Ukrainian art contributed to the formation of its national version in the works of Vasyl Stefanyk. The research applied comparative, biographical methods and method of close reading. The outcome of this detailed analysis demonstrates that the common features of Stefanyk’s antimilitary novels and Western European Expressionists are similar and feature such themes as the crisis of cultural values, anti-military issues, condemnation of murder, states of existential anxiety, tragedy of human existence and eschatological feeling. Furthermore, Expressionists and Stefanyk focus on the psychophysical states of characters ‒ death, madness, injury, numbness, screaming, fear, panic, despair, agony, anxiety, prayer.